A survey of readily accessible perturbation signals for system identification in the frequency domain - GODFREY, K; TAN, A; BARKER, H; CHONG, B (2005)
here has been a rapid increase recently in the number of software packages available to generate different types of perturbation signals for the purpose of system identification in the frequency domain. The types of signal include both computer-optimised signals, which are designed to match a specified power spectrum as closely as possible, and pseudo-random signals, which have fixed spectra. Several of these signals are now readily available directly from the World Wide Web. The objective of this paper is to review what packages are available, and from where, and to outline some of the application areas in which they might be used. (c) 2005 Elsevier Ltd. All rights reserved.